Modulation masking phenomenon for masking signals of different spectral and statistical properties - Kutzner, Dariusz (Archives of Acoustics, 2007)
Modulation masking effect for modulation maskers of different spectral and statisticalproperties was investigated in this study. Three noisebands centred at 16 Hz were used asmodulation maskers, namely: 1) 32-Hz wide Gaussian noise (GN 32 Hz); 2) 32-Hz wide lownoisenoise (LNN 32 Hz) and 3) 4-Hz wide low-noise noise (LNN 4 Hz). The GN 32 Hz andLNN 32 Hz were characterized by the same power spectrum density and different probabilitydensity functions. Conversely, the LNN 32 Hz and LNN 4 Hz had the same probabilitydensity functions, but different power spectrum densities. The root mean square of the modulationmaskers was normalized to 0.2. During the measurements audibility of a sinusoidalprobe modulation presented simultaneously with the modulation maskers was investigated bymeans of the 3AFC adaptive procedure with a 3-down/1-up decision rule. The results of theexperiment indicated that modulation masking was mainly determined by power density spectrumof the modulation masker, however, due to peripheral compression, temporal (statistical)properties of the masker might have played also some role in the modulation masking.